Imidazole propionate ameliorates atopic dermatitis-like skin lesions by inhibiting mitochondrial ROS and mTORC2 - Kim, Ha Eun; Lee, Jong Yeong; Yoo, Dong-Hoon; Park, Hyo-Hyun; Choi, Eun-Ju; Nam, Kyung-Hwa; Park, Jin; Choi, Jin Kyeong (Frontiers in Immunology, 2024)
Imidazole propionate (IMP) is a histidine metabolite produced by some gut microorganisms in the human colon. Increased levels of IMP are associated with intestinal inflammation and the development and progression of cardiovascular disease and diabetes. However, the antiinflammatory activity of IMP has not been investigated. This study aimed to elucidate the role of IMP in treating atopic dermatitis (AD). To understand how IMP mediates immunosuppression in AD, IMP was intraperitoneally injected into a Dermatophagoides farinae extract (DFE)/1-chloro-2,4 dinitrochlorobenzene (DNCB)-induced AD-like skin lesions mouse model. We also characterized the anti-inflammatory mechanism of IMP by inducing an AD response in keratinocytes through TNF-α/IFN-γ or IL-4 stimulation. Contrary to the prevailing view that IMP is an unhealthy microbial metabolite, we found that IMP-treated AD-like skin lesions mice showed significant improvement in their clinical symptoms, including ear thickness, epidermal and dermal thickness, and IgE levels. Furthermore, IMP antagonized the expansion of myeloid (neutrophils, macrophages, eosinophils, and mast cells) and Th cells (Th1, Th2, and Th17) in mouse skin and prevented mitochondrial reactive oxygen species production by inhibiting mitochondrial energy production. Interestingly, we found that IMP inhibited AD by reducing glucose uptake in cells to suppress proinflammatory cytokines and chemokines in an AD-like in vitro model, sequentially downregulating the PI3K and mTORC2 signaling pathways centered on Akt, and upregulating DDIT4 and AMPK. Our results suggest that IMP exerts anti-inflammatory effects through the metabolic reprogramming of skin inflammation, making it a promising therapeutic candidate for AD and related skin diseases.